Mood states and motor performance: a study with high performance voleybol athletes - Lenamar Fiorese Vieira; Saulo Luders Fernandes; José Luiz Lopes Vieira; João Ricardo Nickenig Vissoci (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n1p62 The objective of this research was to investigate the relationship between the sporting performance and mood states of high performance volleyball athletes. Twenty-three adult athletes of both sexes were assessed. The measurement instrument adopted was the POMS questionnaire. Data collection was carried out individually during the state championships. Dada were analyzed using descriptive statistics; the Friedman test for analysis of variance and the Mann-Whitney test for differences between means. The results demonstrated that both teams exhibited the mood state profi le corresponding to the "iceberg" profile. In the male team, vigor remained constant throughout all phases of the competition, while in the female team this element was unstable. The male team's fatigue began low, during the training phase, with rates that rose as the competition progressed, with statistically significant differences between the fi rst and last matches the team played. In the female team, the confusion factor, which was at a high level during training, reduced progressively throughout the competition, with a difference that was signifi cant to p ≤ 0.05. With relation to performance and mood profi le, the female team exhibited statistically significant differences between the mean vigor and fatigue factors of high and low performance athletes. It is therefore concluded that the mood state profi le is a factor that impacts on the motor performance of these high performance teams.